Calcium/Calmodulin Protein Kinase II-Dependent Ryanodine Receptor Phosphorylation Mediates Cardiac Contractile Dysfunction Associated with Sepsis - Sepúlveda, Marisa Noemí (2017)
Objectives: Sepsis is associated with cardiac contractile dysfunction attributed to alterations in Ca2+ handling. We examined the subcellular mechanisms involved in sarcoplasmic reticulum Ca2+ loss that mediate altered Ca2+ handling and contractile dysfunction associated with sepsis. Design: Randomized controlled trial. Setting: Research laboratory Subjects: Male wild type and transgenic mice Interventions: We induced sepsis in mice using the colon ascendens stent peritonitis model. Measurements and Main Results: Twenty-four hours after colon ascendens stent peritonitis surgery, we observed that wild type mice had significantly elevated proinflammatory cytokine levels, reduced ejection fraction, and fractional shortening (ejection fraction %, 54.76 ± 0.67; fractional shortening %, 27.53 ± 0.50) compared with sham controls (ejection fraction %, 73.57 ± 0.20; fractional shortening %, 46.75 ± 0.38). At the cardiac myocyte level, colon ascendens stent peritonitis cells showed reduced cell shortening, Ca2+ transient amplitude and sarcoplasmic reticulum Ca2+ content compared with sham cardiomyocytes. Colon ascendens stent peritonitis hearts showed a significant increase in oxidation-dependent calcium and calmodulin-dependent protein kinase II activity, which could be prevented by pretreating animals with the antioxidant tempol. Pharmacologic inhibition of calcium and calmodulin-dependent protein kinase II with 2.5 μM of KN93 prevented the decrease in cell shortening, Ca2+ transient amplitude, and sarcoplasmic reticulum Ca2+ content in colon ascendens stent peritonitis myocytes. Contractile function was also preserved in colon ascendens stent peritonitis myocytes isolated from transgenic mice expressing a calcium and calmodulin-dependent protein kinase II inhibitory peptide (AC3-I) and in colon ascendens stent peritonitis myocytes isolated from mutant mice that have the ryanodine receptor 2 calcium and calmodulin-dependent protein kinase II-dependent phosphorylation site (serine 2814) mutated to alanine (S2814A). Furthermore, colon ascendens stent peritonitis S2814A mice showed preserved ejection fraction and fractional shortening (ejection fraction %, 73.06 ± 6.31; fractional shortening %, 42.33 ± 5.70) compared with sham S2814A mice (ejection fraction %, 71.60 ± 4.02; fractional shortening %, 39.63 ± 3.23). Conclusions: Results indicate that oxidation and subsequent activation of calcium and calmodulin-dependent protein kinase II has a causal role in the contractile dysfunction associated with sepsis. Calcium and calmodulin-dependent protein kinase II, through phosphorylation of the ryanodine receptor would lead to Ca2+ leak from the sarcoplasmic reticulum, reducing sarcoplasmic reticulum Ca2+ content, Ca2+ transient amplitude and contractility. Development of organ-specific calcium and calmodulin-dependent protein kinase II inhibitors may result in a beneficial therapeutic strategy to ameliorate contractile dysfunction associated with sepsis.